The Use of Balanced Scorecard in Achieving Total Quality in Technical Colleges for Girls in the Kingdom of Saudi Arabia: A field study - Kasnawi, Nada Ahmad; Obaid, Rawia Rida (Journal of Economic, Administrative and Legal Sciences, 2021)
The Balanced Scorecard is a comprehensive strategic system designed to measure performance in four dimensions: financial customer, internal processes, and learning and growth. Accordingly, this research examines the extent to which the application of Balanced Scorecards is used to evaluate the performance of employees To achieve total quality in the Technical Colleges for Girls in the Kingdom of Saudi Arabia, to achieve that, the researcher followed the inductive approach in the theoretical part of the research, followed by the use of the analytical descriptive approach for the empirical part of the study. The empirical part of the current study is conducted through the design and distribution of questionnaire to 148 female employees in leadership positions at technical colleges for girls in Saudi Arabia, of which 63 is fully completed and recovered. The questionnaire is divided into five sections. The first was related to the bibliography of respondents and information of college's structure. The second is related to the contribution of the balanced performance card in achieving the strategic and operational goals of colleges. The third section covers requirements for technical colleges to apply the balanced scorecard. The fourth is related exploring the obstacles that would limit the application of the scorecards effectively. Finally, the fifth section, reflects leader’s perception of applying the scorecard in evaluating activities in technical colleges. The results are analyzed using the statistical program (Spss.V19). Where the results confirmed that the dimensions of the balanced scorecard are largely appropriate to achieve the requirements of the college’s short-term and long-term strategic goals, by approximately 54%. Most of the college leaders agreed on the availability of the elements of applying the dimensions of the balanced scorecard in technical colleges for girls with a percentage of 61.9%. The results confirmed the support of college administrations to implement the balanced scorecard by 50.8% in order to overcome the obstacles that limit the application of the Balanced Scorecard in colleges. The results also confirmed that the application of the Balanced Scorecard helps in identifying the departments that need to improve the performance of the college and the application of the Balanced Scorecard helps the college administration in evaluating the growth and learning of the employees with a rate of 47.6%. The results of the research concluded that the Technical Colleges Administration for Girls supports the application of the Balanced Scorecard, as this helps identify the departments that need to improve performance. The results have shown that all the necessary ingredients for implementing a balanced scorecard are available in most technical colleges for girls, and college administrations strive to overcome all obstacles that could limit this. Based on the previous results, several recommendations can be suggested, such the strategic objectives of colleges must be in agreement with the dimensions of the balanced scorecard to achieve the desired results. It can be suggested as well that the dimensions of the scorecards should be flexible to any technical, professional or community developments.
Keywords: balanced scorecard; total quality; technical colleges